Plant growth promoting bacteria (PGPB)-induced plant adaptations to stresses: an updated review - Fanai, Awmpuizeli; Bohia, Beirachhitha; Lalremruati, Felicia; Lalhriatpuii, Nancy; Lalrokimi; Lalmuanpuii, Rosie; Singh, Prashant Kumar; Zothanpuia (PeerJ, 2024)
Plants and bacteria are co-evolving and interact with one another in a continuous process. This interaction enables the plant to assimilate the nutrients and acquire protection with the help of beneficial bacteria known as plant growth-promoting bacteria (PGPB). These beneficial bacteria naturally produce bioactive compounds that can assist plants’ stress tolerance. Moreover, they employ various direct and indirect processes to induce plant growth and protect plants against pathogens. The direct mechanisms involve phytohormone production, phosphate solubilization, zinc solubilization, potassium solubilization, ammonia production, and nitrogen fixation while, the production of siderophores, lytic enzymes, hydrogen cyanide, and antibiotics are included under indirect mechanisms. This property can be exploited to prepare bioformulants for biofertilizers, biopesticides, and biofungicides, which are convenient alternatives for chemical-based products to achieve sustainable agricultural practices. However, the application and importance of PGPB in sustainable agriculture are still debatable despite its immense diversity and plant growth-supporting activities. Moreover, the performance of PGPB varies greatly and is dictated by the environmental factors affecting plant growth and development. This review emphasizes the role of PGPB in plant growth-promoting activities (stress tolerance, production of bioactive compounds and phytohormones) and summarises new formulations and opportunities.
Keywords: Plant growth-promoting microbes; Biotic stress; Abiotic stress; Bioactive compound; Phytohormones; Bioformulations